Pilot of the BOOST-A™: An online transition planning program for adolescents with autism - Hatfield, M.; Murray, N.; Ciccarelli, M.; Falkmer, Torbjorn; Falkmer, M. (Wiley-Blackwell Publishing Asia, 2017)
© 2017 Occupational Therapy Australia. Background: Many adolescents with autism face difficulties with the transition from high school into post-school activities. The Better OutcOmes & Successful Transitions for Autism (BOOST-A™) is an online transition planning program which supports adolescents on the autism spectrum to prepare for leaving school. This study describes the development of the BOOST-A™ and aimed to determine the feasibility and viability of the program. Methods: Two pilot studies were conducted. In Pilot A, the BOOST-A™ was trialled by six adolescents on the autism spectrum, their parents, and the professionals who worked with them, to determine its feasibility. In Pilot B, 88 allied health professionals (occupational therapists, speech pathologists, and psychologists) reviewed the BOOST-A™ to determine its viability. Results: Participants rated the BOOST-A™ as a feasible tool for transition planning. The majority of allied health professionals agreed that it was a viable program. Based on participant feedback, the BOOST-A™ was modified to improve usability and feasibility. Conclusion: The BOOST-A™ is a viable and feasible program that has the potential to assist adolescents with autism in preparing for transitioning out of high school. Future research will determine the effectiveness of the BOOST-A™ with adolescents across Australia.